KETERBUKAAN INFORMASI PUBLIK: HOLISTIKASI DAN AKSELERASI GOOD GOVERNANCE - Ricky Ricky; Muhammad Tanzil Aziz Rahimallah (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
This study aims to describe the importance of public information disclosure in the context of achieving good governance and how the efforts that can be made by the Public Information Commission at the central and regional levels in encouraging public information disclosure and the realization of an information society in Indonesia. The research method uses a literature study by analyzing the contents of concepts (content analysis) and theories related to public information disclosure and good governance so that the correlation between the two can be determined. The results of the study show that the implementation of public information disclosure is one of the most effective ways in accelerating and expanding the implementation of good governance (accountability, transparency and public participation) in the government system in Indonesia. On the other hand, stakeholders can only synergize and work together in conditions that are far more conducive when there is access to information that is equal and can be accessed freely. Therefore, it is necessary to encourage the role of institutions that can guarantee and be responsible for the implementation of public information disclosure in this case the Information Commission is a priority especially in the era of globalization and technological developments as it is today